Door-to-door survey of major neurological disorders (project) in Al Quseir City, Red Sea Governorate, Egypt - El Tallawy HN (Dove Medical Press, 2013)
Hamdy NA El Tallawy,1 Wafaa MA Farghaly,1 Tarek A Rageh,1 Ghaydaa A Shehata,1 Reda Badry,1 Nabil A Metwally,2 Esam A El Moselhy,2 Mahmoud Hassan,2 Mohamed A Sayed,3 Ahmed A Waris,1 Yaser Hamed,2 Islam Shaaban,2 Mohamed A Hamed,1 Mahmoud Raafat Kandil11Department of Neurology, Faculty of Medicine, Assiut University, Assiut, Egypt; 2Department of Neurology and Public Health, Faculty of Medicine, Al-Azhar University (Assiut branch), Assiut, Egypt; 3Department of Neurology, Faculty of Medicine, Sohag University, Sohag, EgyptAbstract: A door-to-door survey, including every household, was conducted for all inhabitants of Al Quseir City (33,283), Red Sea Governorate, Egypt by three specialists of neurology as well as nine senior staff members of neurology and 15 female social workers to assess the epidemiology of major neurological disorders. Over six phases, from July 1, 2009 to January 31, 2012, screening of all eligible people in the population was carried out, by which case ascertainment of all major neurological disorders included in the study was done according to the accepted definitions and diagnostic criteria of the World Health Organization. The order of frequency of prevalence of the studied neurological disorders was dementia (3.83% for those aged > 60 years), migraine (2.8% for those aged > 8 years), stroke (6.2/1000 for those aged > 20 years), epilepsy (5.5/1000), Parkinson’s disease (452.1/100,000 for those aged > 40 years), cerebral palsy (3.6/1000 among children < 18 years), spinal cord disorders (63/100,000) dystonia (39.11/100,000), cerebellar ataxia (30.01/100,000), trigeminal neuralgia (28/100,000 for those aged > 37 years), chorea (21.03/100,000), athetosis (15/100,000), and multiple sclerosis (13.74/100,000). The incidence rates of stroke, epilepsy, and Bell’s palsy were 181/100,000, 48/100,000, and 98.9/100,000 per year, respectively.Keywords: prevalence, incidence, neurological disorders